Influence of silica source in the catalytic activity and heterogenity of mesoporous vanadosilicates - Shylesh, S.; Mirajkar, Subhash P.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Vanadium-substituted ordered mesoporous silicates (V-OMS) were synthesized hydrothermally using two common silica sources, viz. fumed silica and tetraethyl orthosilicate, and their surface properties and catalytic activities were evaluated in the liquid phase oxidation of 1-napthol using aqueous H2O2 as an oxidant. The catalysts were characterized by XRD, N-2, adsorption-desorption, DRUV-vis and TPR to evaluate the mesostructural ordering and the local environment of vanadium in the MCM-41 matrix. Characterization data of the fresh calcined catalysts reveal a more ordered hexagonal structure for the V-MCM-41 catalyst prepared by using tetraethyl orthosilicate as the silica source while spent catalyst showed that the material is less stable than the V-MCM-41 catalyst prepared by using fumed silica as the silica source. Further, the observed differences in the selectivity behavior of extracted and calcined forms of both vanadium catalysts shows that the treatment conditions had a decisive role in the formation of extra framework metal species and further in the mesoscopic structural ordering. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-napthol; MCM-41; Mesoporous; Oxidation; Vanadium

Vanadium-containing ordered mesoporous silicas: synthesis, characterization and catalytic activity in the hydroxylation of biphenyl - George, J.; Shylesh, S; Singh, AP (Applied Catalysis A - General, 2005)
A series of vanadium-containing ordered mesoporous MCM-41 materials (V-OMS) have been synthesized by direct hydrothermal (VMCM-41) and grafting (V/MCM-41) methods using hexadecyl trimethyl ammonium bromide (HDTMABr) as the structure-directing agent. The physico-chemical properties of the vanadium-containing materials were characterized in detail by ICP-OES, XRD, Fr-IR, N-2 adsorption-desorption, DRUV-VIS, TPR, XPS and SEM techniques. The redox performances of the vanadium-modified mesoporous materials were tested in the hydroxylation of biphenyl using aqueous H2O2 (30 wt.%) as oxidant. For a better exploitation of the catalytic activity, the reaction parameters are optimized in terms of temperature, solvent, oxidant, etc. A comparison between the catalytic activity values of the vanadium-containing mesoporous materials prepared by the two routes shows that vanadium-substituted (V-MCM-41) materials had increased activity and improved selectivity for mono hydroxyl products in the hydroxylation reaction of biphenyl compared to the V/MCM-41 catalysts. The heterogenity of the catalysts was verified by a series of leaching studies. Both the catalysts enhance the leaching of active vanadia species during the reaction; among them, V/MCM-41 shows the least heterogenity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biphenyl; heterogenity; MCM-41; Mesoporous molecular sieves; Vanadium

Vanadium-containing ordered mesoporous silicates: does the silica source really affect the catalytic activity, structural stability, and nature of vanadium sites in V-MCM-41? - Shylesh, S; Singh, AP (Journal of Catalysis, 2005)
A series of vanadium-substituted mesoporous materials were synthesized hydrothermally with the use of two commonly used silica Sources. fumed silica and tetra ethyl orthosilicate. The extent of mesopore structural ordering was confirmed from X-ray diffraction, N-2 physisorption, SEM, and TEM, and the presence and nature of vanadium species inside the framework of the MCM-41 matrix was confirmed in detail with the use of various characterization techniques like FT-IR, Si-29 MAS NMR, DRUV-vis, EPR, V-51 MAS NMR, and Raman analysis. It is deduced from the above characterization techniques that, regardless of the silica source, vanadium is incorporated into the silica framework and thereby increases the structural ordering and wall thickness of the mesoporous material. Thermal and hydrothermal Studies performed over the V-MCM-41 catalysts show that the Si-O-Si inorganic backbone from a fumed silica source is more resistant to severe thermal treatments and hydrolysis than the tetraethyl orthosilicate-synthesized catalysts. Spectroscopic characterization reveals the existence of easily accessible isolated tetrahedral vanadium sites on V-MCM-41 catalyst prepared front fumed silica catalyst, whereas the sample obtained from a tetraethyl orthosilicate silica Source shows vanadium in more disordered sites. Catalytic results show that both catalysts display excellent activity toward the epoxidation reaction of bulkier olefins, and the exceptional activity of the fumed silica catalyst may arise from the more isolated tetrahedral sites and the complementary textural characteristics, which may facilitate the easy access of substrate to the isolated framework metal sites. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: epoxidation; fumed silica; MCM-41; tetraethyl orthosilicate; Vanadium

Heterogenized vanadyl cations over modified silica surfaces: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous and amorphous silica supports - Shylesh, S.; Singh, A. R. (Journal of Catalysis, 2006)
Using a postsynthesis grafting method, 3-aminopropyltriethoxysilane (3-APTS) was functionalized over silica gel and mesoporous silica materials like SBA-15 and MCM-41. Vanadyl cations were then immobilized over the functionalized amino groups of the silica samples and used as a catalyst in the liquid-phase oxidation reaction of cyclohexane. Elemental analysis, PXRD, TEM, N-2 adsorption-desorption isotherms, FTIR, C-13 and Si-29 MAS NMR, UV-vis, and EPR techniques were used to characterize the developed materials. Characterization results suggest that the percentage of 3-APTS grafting depends on the number of isolated and genlinal silanol sites of the support material, the solvents used during the grafting reactions, and the sample pretreatment conditions. We found that using toluene as the dispersing medium and Si-MCM-41 as a support provides the maximum amount of amine functionalization, and thereby the highest percentage of vanadium immobilization. Catalytic activity and metal leaching studies show that vanadium-immobilized mesoporous solids are more active and stable than the silica gel-functionalized vanadium catalyst and a framework-substituted V-MCM-41 catalyst. The enhanced activity and stability of the immobilized vanadium catalysts compared with the V-MCM-41 and silica gel samples are attributed to the active metal site isolations, as well as to the spatial restrictions imparted from the concave silica surfaces of the mesoporous solids rather than the convex silica surfaces of the silica gel sample. (c) 2006 Published by Elsevier Inc.
Keywords: 3-APTS; mesoporous solids; Oxidation; Silica gel; Vanadium

Novel vanadium n-propylamino phosphate catalyst: synthesis, characterization and applications - Anumula, Rajini; Nookaraju, Muralasetti; Selvaraj, Kaliaperumal; Reddy, Ingala Ajit Kumar; Narayanan, Venkatathri (Materials Research-Ibero-American Journal of Materials, 2013)
A novel, lamellar type Vanadium n-propylamino phosphate catalyst is synthesized and characterized by using various physicochemical techniques such as Powder X-ray diffraction, Scanning electron microscopy/Energy dispersive X-ray analysis, Thermogravimetry/Differential thermal analysis, Fourier transform Infrared analysis, Electron spin resonance spectroscopy, Ultraviolet - Visible Diffuse reflectance spectroscopy, X-ray Photoelectron spectroscopy, P-31 Magic angle spinning Nuclear Magnetic Resonance spectroscopy and Catalytic applications toward Octahydroquinazolinone synthesis. It is found that the n-propylamine is present as sandwich between Vanadyl phosphate layers. Most of the Vanadium is present as V4+ ions in tetrahedral co-ordination. Vanadium n-propylamino phosphate catalyses Octahydroquinazolinone synthesis more effeciently and the optimum conditions required for Octahydroquinazolinone synthesis are, Benzaldehyde (2 mmol), Dimedone (2 mmol), Urea (4 mmol), Methanol + Water (1:1, 5 mL) and Catalyst (0.05 g). A plausible mechanism is also proposed.
Keywords: n-propylamino phosphate; octahydroquinazolinones; synthesis; Vanadium

Ambient oxidation of benzene to phenol by photocatalysis on Au/Ti0.98V0.02O2: role of holes - Devaraji, Perumal; Sathu, Naveen K.; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
A potential photocatalyst with 2 atom % vanadium incorporated into the 1 lattice of disordered mesoporous titania, Ti0.98V0.02O2, (TV2) was synthesized. Au was deposited on TV2 (Au/TV2) through a photodeposition method. Structural, microscopy, and spectroscopy techniques support the incorporation of vanadium into the TiO2 lattice, and Au was deposited on the surfaces of TV2. Photocatalytic oxidation of benzene was conducted at ambient temperature under UV and/or visible light to demonstrate the catalytic activity of the Au/TV2 catalyst. The TV2 lattice exhibits a quantum jump in benzene to phenol oxidation compared to that of TiO2, highlighting the importance of V for oxidation. Introduction of Au onto TV2 further increases the benzene to phenol oxidation and phenol yield by a factor of 2 under UV light compared to those of bare TV2. No significant phenol production was observed in visible light with or without gold, indicating the role of gold is indirect toward charge separation and electron storage. Nano gold clusters on TV2 selectively store photoexcited electrons and in turn maximize holes utilization on TiO2. The high photocatalytic activity of Au/TV2 is mainly attributed to the presence of Schottky junctions, disordered mesoporosity, and short diffusion lengths for charge carriers.
Keywords: nano gold; phenol; Photocatalysis; Schottky junction; titania; Vanadium

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium